PENJUALAN BERSIH DAN BEBAN KOMERSIAL TERHADAP PAJAK PENGHASILAN TERUTANG PADA PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2020 - Sembiring, Yan Christin Br; Saragih, Afni Eliana; Ketaren, Chintya Marselina Br (Jurnal Riset Akuntansi & Keuangan, 2023)
This study aims to empirically test whether Net Sales And Commercial Expenses On Income Tax Payable In Basic Industrial And Chemical Sector Companies Listed On The Indonesia Stock Exchange For The 2017-2020 Period. The population of this study were 73 companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange in 2017-2020. The sample in this study was obtained by purposive sampling, with a sample of 20 companies. Data collection techniques used documentation techniques. The analysis method used was linear regression equation multiple by using the SPSS 24 program. From the test results using SPSS, it is known that the coefficient of determination (R Square) of 0.233 means that sales and commercial expenses together affect the income tax payable, namely 76.7%. Based on the results of the analysis of multiple linear regression equations, it can be concluded that (1) net sales have a positive and significant effect on income tax payable in the Basic and Chemical Industry Sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period (2) commercial materials have a negative and insignificant effect on income tax payable to companies in the Basic and Chemical Industry Sector listed on the Indonesia Stock Exchange Period 2017-2020